Immune Checkpoint Molecules—Inherited Variations as Markers for Cancer Risk - Wagner, Marta; Jasek, Monika; Karabon, Lidia (Frontiers in Immunology, 2021)
In recent years, immunotherapy has been revolutionized by a new approach that works by blocking receptors called immune checkpoints (IC). These molecules play a key role in maintaining immune homeostasis, mainly by suppressing the immune response and by preventing its overactivation. Since inhibition of the immune response by IC can be used by cancer to avoid recognition and destruction by immune system, blocking them enhances the anti-tumor response. This therapeutic approach has brought spectacular clinical effects. The ICs present heterogeneous expression patterns on immune cells, which may affect the effectiveness of immunotherapy. The inherited genetic variants in regulatory regions of ICs genes can be considered as potential factors responsible for observed inter-individual differences in ICs expression levels on immune cells. Additionally, polymorphism located in exons may introduce changes to ICs amino acid sequences with potential impact on functional properties of these molecules. Since genetic variants may affect both expression and structure of ICs, they are considered as risk factors of cancer development. Inherited genetic markers such as SNPs may also be useful in stratification patients into groups which will benefit from particular immunotherapy. In this review, we have comprehensively summarized the current understanding of the relationship between inherited variations of CTLA-4, PDCD1, PD-L1, BTLA, TIM-3, and LAG-3 genes in order to select SNPs which can be used as predictive biomarkers in personalized evaluation of cancer risk development and outcomes as well as possible response to immunotherapy.